A D3Q27 multiple-relaxation-time lattice Boltzmann method for turbulent flows. (March 2015) - Suga, K.; Kuwata, Y.; Takashima, K.; Chikasue, R.
Abstract A three-dimensional twenty-seven (D3Q27) discrete velocity multiple-relaxation-time lattice Boltzmann method is developed. The proposed scheme is validated in fully developed turbulent channel, pipe and porous medium flows through direct and large eddy simulations. The direct numerical simulation of the turbulent channel flow confirms that the present scheme is as reliable as the spectrum method for simulating turbulence. Through the large eddy simulations of the pipe and porous medium flows, the present scheme shows its satisfactory accuracy for simulating turbulent flows bounded by circular walls that is failed by the three-dimensional nineteen (D3Q19) model.